Study on Wellbore Temperature and Pressure Distribution in Process of Gas Hydrate Mined by Polymer Additive CO2 Jet - Minghui Wei; Chenghuai Wu; Yanxi Zhou (Advances in Polymer Technology)
In order to solve the problem of hydrate reservoir collapse and hydrate regenerated in the process of solid fluidization of natural gas hydrate, a new method of natural gas hydrate exploit by high‐polymer additive (low viscosity carboxymethyl cellulose LV‐CMC) carbon dioxide jet was proposed. The wellbore temperature and pressure changes during this process are analyzed, and the wellbore temperature and pressure model are established and solved by the state space method. This paper also analyzed the effects of relevant parameters on hydrate decomposition, such as injection flow, temperature, and pressure. The results show that increasing the injection pressure allows the hydrate decomposition site to be closer to the annulus outlet. Compared with water, with polymer additive CO2 fluid as the drilling fluid, the intersection point of phase equilibrium curve and annular pressure curve is closer to annular outlet, which is obviously more conducive to well control. In order to avoid phase changes, the injection pressure of the carbon dioxide fluid of the high‐polymer additive should not be lower than 10 MPa, and the injection temperature should not be higher than 285 K.